Investigation of improvements to city areas of importance to the implementation of clean water - Milanie, Feby (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
In the context of improving urban areas through clean water services, the provision and distribution of clean water systems are the primary focus of this research. The study aims to identify effective methods to enhance clean water services. Following the PRISMA guidelines for systematic reviews and meta-analyses, the study searched four major databases: Scholar, ResearchGate, Scopus, and Taylor & Francis Online. The search process used relevant keywords such as "clean water services" OR "water distribution systems," OR "water quality improvement" across each database. From 967 articles initially identified, four articles were selected after a rigorous selection process applying inclusion and exclusion criteria. Key findings highlight that the use of sensors to monitor water quality parameters such as pressure, flow, pH, chlorine, and turbidity; the application of the elitist nondominated sorting genetic algorithm (NSGA-II); and active community involvement with government support are effective in improving the quality and distribution of clean water. Further research is recommended to focus on developing more advanced sensor technologies, deeper studies on NSGA-II implementation, strategies to enhance community involvement, policy analyses that support these efforts, and collaborative models involving government, private sector, and communities. Thus, sustained efforts in this research are expected to significantly contribute to improving clean water services in various urban areas.